Preface and Statement of Peer Review - Gabriele Ciccone; Giuseppe Guarino (Proceedings)
On 15 and 16 December 2022, the Sala della Fortuna of the National Etruscan Museum of Villa Giulia in Rome hosted the second edition of the conference entitled “Una Quantum 2022: Open Source Technologies for Cultural Heritage, Cultural Activities, and Tourism”, funded by the General Directorate of Education, Research, and Cultural Institutes of the MIC [...]